2017
DOI: 10.2166/wcc.2017.148
|View full text |Cite
|
Sign up to set email alerts
|

Estimating evapotranspiration using the complementary relationship and the Budyko framework

Abstract: Evapotranspiration is the single most important mechanism of mass and energy exchange between atmosphere, biosphere, and hydrosphere. Among the common approaches to estimating evapotranspiration, the complementary relationship has been the subject of many recent studies given its simplicity and the use of meteorological data only. Recently, a modified version of the complementary relationship, Modified GG, was developed using meteorological data only and had been successfully applied at 34 diverse global sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 63 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…[30]. Figure 2 presents the results obtained from Kim [26]. These results are in agreement with Anayah [15], which showed that the modified GG model needs further improvements in dry conditions, and showed the lowest mean RMSE in both dry and wet sites.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…[30]. Figure 2 presents the results obtained from Kim [26]. These results are in agreement with Anayah [15], which showed that the modified GG model needs further improvements in dry conditions, and showed the lowest mean RMSE in both dry and wet sites.…”
Section: Introductionsupporting
confidence: 77%
“…These results are in agreement with Anayah [15], which showed that the modified GG model needs further improvements in dry conditions, and showed the lowest mean RMSE in both dry and wet sites. Overall, these results indicate that, among the groundbased methods [26], model can be used as a powerful methodology to estimate ET. While these findings are good within the realm of complimentary methods (or ground-based methods), some of the more commonly used ET estimation methods now use remote sensing data.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…11A, D) fall most closely to the 1:1 line, but the residuals ( fig. 11D) (Reitz and others, 2017;Kim, 2017) have shown that at low ET measurements, the SSEBop method underestimates ET, and at higher ET measurements, the SSEBop method overestimates ET. The estimation bias for the SSEBop method could account for at least some of the skewness in the SWB model results because the errors are in the same direction as they are when comparing actual ET measurements to the SSEBop estimates.…”
Section: Model Fit-comparison To Observationsmentioning
confidence: 94%